Assessing Literary Heritage Policies in the Context of Creative Cities - Arcos-Pumarola, Jordi (Journal of Tourism, Sustainability and Well-being, 2019)
This paper focuses on Creative Cities of Literature of United Nations Educational, Scientific and Cultural Organization (UNESCO) and analyses how the policies and actions of the cities in this network can contribute to their cultural environment. It builds a mixed theoretical framework that looks at UNESCO’s Creative Cities Network, the Educating Cities Network and the European Heritage Strategy for the 21st Century. Then, to establish a set of recommendations that assesses the management of literary heritage in creative cities of literature, we have carried out a two-phase content analysis of the participating cities’ monitoring reports. In the first phase, the analysis is found on the specific criteria of cities of literature that are already part of UNESCO’s Creative Cities Network. In the second phase, the analysis is based on the list of challenges and recommendations defined by the European Heritage Strategy for the 21st century. This analysis shows that the City of Literature programme as a whole is a database of best practices for developing an urban literary environment. The article presents a set of actions to enhance the cultural environment of a literary city by focusing on its use of its literary heritage.